Air Quality and Source Apportionment - Rebecca Sheesley (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Atmospheric particulate matter (PM) is known to have far-ranging impacts on human health through to climate forcing. The characterization of emission sources and the quantification of specific source impacts to PM concentrations significantly enhance our understanding of, and our ability to, eventually predicting the fate and transport of atmospheric PM and its associated impacts on humans and the environment. Recent advances in source apportionment applications have contributed unique combinations of chemical and numerical techniques for determining the contributions of specific sources, including diesel exhaust and biomass burning. These advances also identify and help characterize the contributions of previously uncharacterized sources. Numerical modeling has also enabled estimations of contributions of emission sources to atmospherically processed PM in urban and rural regions. Investigation into the emissions sources driving air quality is currently of concern across the globe. This Special Issue offers studies at the intersection of air quality and source apportionment for study areas in China, Germany, Iceland, Mexico, and the United States. Studies cover diverse methods for chemical characterization and modeling of the impact of different emission sources on air quality.